Designing PDE software for vector computers as a “data flow algorithm” - Schönauer, W.; Schnepf, E.; Müller, H. (Computer physics communications, 1985)
The best we can do on existing vector computers is to device algorithms which maintain a continuous data flow. For large 3-D problems the I/O is the decisive bottleneck. An optimal data structure for each separate task is the key for an efficient algorithm. How to devise such algorithms for the solution of large 3-D elliptic problems by the finite difference method is demonstrated in the paper.